A 'debt' based approach to land degradation as an indicator of global change. (3rd September 2021) - Wuepper, David; Borrelli, Pasquale; Panagos, Panos; Lauber, Thomas; Crowther, Thomas; Thomas, Amy; Robinson, David A.
Abstract : We propose a way to synthesize different approaches to globally map land degradation by combining vegetation and soil indicators into a consistent framework for assessing land degradation as an environmental 'debt'. our combined approach reveals a broader lens for land degradation through global change, in particular, identifying hot‐spots for the different kinds of land degradation.